2018
DOI: 10.1177/014556131809700311
|View full text |Cite
|
Sign up to set email alerts
|

“Split to Save”: Accessing Mandibular Lesions using Sagittal Split Osteotomy with Virtual Surgical Planning

Abstract: Large. benign intramandibular lesions arefrequently removed by resection followed by extensive free tissue transfer or delayed bone grafting. We outline a protocol to remove benign mandibular lesions usingsagittal split osteotomy (SSO) with virtual surgical planning (VSP) to mitigate risks involved with this effective. tissue-saving approach. Patients with benign mandibular lesions accessed by SSO with VSP during 2014 were included in this study. Computed tomographic data were imported into VSPsoftware. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…To access a benign mandibular tumor, Liu et al [10] used sagittal split osteotomy and VSP, in which they identified the precise pathway of the entire IAN canal and the location of the tumor. After excising the benign tumor, they fixed the osteotomy segments with screws and a plate.…”
Section: Discussionmentioning
confidence: 99%
“…To access a benign mandibular tumor, Liu et al [10] used sagittal split osteotomy and VSP, in which they identified the precise pathway of the entire IAN canal and the location of the tumor. After excising the benign tumor, they fixed the osteotomy segments with screws and a plate.…”
Section: Discussionmentioning
confidence: 99%